Cry of the earth, of the poor, and of the spirit. Physical, ethical, and spiritual dimensions of the ecological crisis - Kureethadam , Joshtrom Isaac (Studia Ecologiae et Bioethicae, 2014)
The article offers a comprehensive understanding of the contemporary ecological crisis from a scientific, moral, and theological perspective. The physical dimension of the crisis is evident in the host of authoritative warnings from the scientific community in recent years. !e crisis is also ethical for the fact that its disproportionate victims are the poor communities who have contributed least to causing the problem in the first place. At a still deeper level, the ecological crisis is also a profoundly spiritual crisis, as it results primarily from our inability to look at the physical world as God’s creation, the primordial revelation of divine goodness and glory. !e author skillfully weaves together the physical, moral, and religious dimensions of the problem into a unitary whole, and argues that it is only a holistic view of the crisis that can awaken us to the true magnitude of the unprecedented challenge facing our common home.